ANALISIS EFEKTIVITAS PENAGIHAN PAJAK DENGAN SURAT PAKSA DALAM UPAYA MENINGKATKAN PENERIMAAN PAJAK DI KPP PRATAMA JAKARTA SENEN TAHUN 2023 - Naimah, Milhatun; Rahmi, Notika (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This research was based on the fact that there were still many taxpayers who were disobedient and did not have the ability to pay their tax debts, so that caused high tax arrears which caused low tax revenues. This research aimed to know the level of effectiveness of tax collection by using forced letters in an effort to increase tax revenue at KPP Pratama Senen Jakarta in 2023. The research method used was qualitative with data collection techniques through observation, interviews and documentation. The research results showed that the effectiveness in 2021 it reached 25%, in 2022 it reached 31%, and in 2023 it reached 20%. From the research results, it could be concluded that tax collection by using forced letters in an effort to increase tax revenue at KPP Pratama Senen Jakarta was classified as ineffective. This was because there were still many taxpayers who were negligent and also taxpayers who did not have the ability to pay their tax debts. Efforts that must be made were to increase human resources, as well as carried out continuous socialization to raise the awareness of taxpayers in fulfilling their tax obligations in paying off their tax debts.